The Pan-Pacific Planet Search – VIII. Complete results and the occurrence rate of planets around low-luminosity giants. Issue 4 (4th December 2019) - Wittenmyer, Robert A; Butler, R P; Horner, Jonathan; Clark, Jake; Tinney, C G; Carter, B D; Wang, Liang; Johnson, John Asher; Collins, Michaela
ABSTRACT: Our knowledge of the populations and occurrence rates of planets orbiting evolved intermediate-mass stars lags behind that for solar-type stars by at least a decade. Some radial velocity surveys have targeted these low-luminosity giant stars, providing some insights into the properties of their planetary systems. Here, we present the final data release of the Pan-Pacific Planet Search (PPPS), a 5 yr radial velocity survey using the 3.9 m Anglo-Australian Telescope. We present 1293 precise radial velocity measurements for 129 stars, and highlight 6 potential substellar-mass companions, which require additional observations to confirm. Correcting for the substantial incompleteness in the sample, we estimate the occurrence rate of giant planets orbiting low-luminosity giant stars to be approximately 7.8^+9.1_-3.3 per cent. This result is consistent with the frequency of such planets found to orbit main-sequence A-type stars, from which the PPPS stars have evolved.